The effectiveness of the use of xenogeneic bone blocks mixed with autologous Concentrated Growth Factors (CGF) in bone regeneration techniques: a case series - E. Gheno; A. Palermo; L.F. Rodella; B. Buffoli (Ariesdue, 2014)
Aim: Different types of biomaterials and surgical techniques are currently used for the augmentation of atrophic ridges in view of implant supported restorations. The aim of this study was to clinically and histologically evaluate the combination of Concentrated Growth Factors (CGF) and xenogeneic bone in vertical and/or horizontal ridge augmentation. Materials and methods: Seven patients (3 males and 4 females), who required oral implant and ridge augmentation surgery, were selected: 3 implants were placed during the surgery and 4 implants were inserted 4 months later, in order to allow complete graft integration. All implants were loaded after a 4-month healing time. The following parameters were assessed: a) the capability of CGF to permeate the bone scaffold; b) the degree of bone regeneration; c) the clinical success rate. Results: The results obtained showed that: a) with the used medical device porous bone scaffolds can be effectively permeated by the CGF; b) the permeated grafting material resulted in effective bone regeneration, as confirmed by histomorphometric analysis; c) all implants were successfully in function at the 12 months follow-up. Conclusion: This technique can be safely performed in the dental office under local anesthesia, so it can be considered a viable option in bone regeneration surgery.